Regulation of large airports: Status quo and options for reform - Hans-Martin Niemeier (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2009)
Over the last 25 years, the governance structure of airports has changed in many parts of the world. Today airports are no longer a homogenous group of public utilities, but a heterogeneous group with ownership structures ranging from state-owned to partial and even full privatisation, with regulatory systems ranging from cost regulation to price cap and even to complete deregulation and with different degrees of competition, ranging from pure monopolistic to oligopolistic markets. Airports, even publicly owned airports, have become more commercialized and more profit oriented. Thus, the upstream markets within the vertical air transport supply chain followed the trend set by the downstream markets, as the airline industry underwent these changes earlier and many ('downstream') air transport markets are now characterized by fierce competition between airlines (Winston and de Rus, 2008). These changes have put the airline/airport relationship under stress. The vertical relationship of the aviation industry does not resemble the smoothly operating supply chains of other industries, but more like the opposite of a perfect supply that chain managers learn to operate in their MBA courses. It has lead to a heated debate over airport regulation and the rules that determine the quality, quantity and price of airport services for airlines. IATA claims that airports are natural monopolies which are ineffectively regulated and which 'are exploiting, in many cases, their natural monopoly position' (IATA, 2007, p. 2.). The ACI response to this is that airports are a competitive industry which should not be regulated at all. The Association of German Airports argues for example that today, in Germany, 'airports are in tough competition and therefore the level of airport charges is determined by market mechanisms' (translation by author) (ADV, 2007, p 2). The OECD has taken up this issue and asked for some scientific guidance. The objective of this paper is to provide criteria, information and concepts for an objective discussion and dialogue between airports, airlines, regulator, governments and the general public but with specific reference to gateway airports. The focus is on gateway, airports which provide access to a country for international passengers and/or cargo. Therefore the analysis confines itself to the regulation of hubs and secondary airports. The latter are included because they provide some competition to hubs, although they are not gateways in the strict sense. On the contrary, no small airports, nor those that serve only regions with a small population density, nor secondary ones within metropolitan regions, will be considered. In the first section the paper develops the criteria to evaluate regulation. It then provides an overview on the performance of airports. In the third section rationale for airport regulation are discussed. Thereafter the alternative to regulation will be analysed. Can competition among airports substitute regulation, or is the competition between gateway airports not sufficiently intense? In the fifth section, the strength and weaknesses of different regulatory regimes are evaluated and options for a reform are discussed. The paper closes with a summary.
Keywords: 330